Measurement of inclusive J/[psi] suppression in Au+Au collisions at √sNN=200 GeV through the dimuon channel at STAR - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physics letters, 2019)
J/ψ suppression has long been considered a sensitive signature of the formation of the Quark-Gluon Plasma (QGP) in relativistic heavy-ion collisions. In this letter, we present the first measurement of inclusive J/ψ production at mid-rapidity through the dimuon decay channel in Au+Au collisions at sNN=200 GeV with the STAR experiment. These measurements became possible after the installation of the Muon Telescope Detector was completed in 2014. The J/ψ yields are measured in a wide transverse momentum (pT) range of 0.15 GeV/c to 12 GeV/c from central to peripheral collisions. They extend the kinematic reach of previous measurements at RHIC with improved precision. In the 0-10% most central collisions, the J/ψ yield is suppressed by a factor of approximately 3 for pT>5 GeV/c relative to that in p+p collisions scaled by the number of binary nucleon-nucleon collisions. The J/ψ nuclear modification factor displays little dependence on pT in all centrality bins. Model calculations can qualitatively describe the data, providing further evidence for the color-screening effect experienced by J/ψ mesons in the QGP.
Im Titel ist "chi" als griechischer Buchstabe dargestellt
Im Titel steht der ganze Ausdruck "snn" unter dem Wurzelzeichen
Im Titel ist der Buchstabe "s" hochgestellt
Gesehen am 24.10.2019